IMPROVING STUDENTS’ PRONUNCIATION THROUGH SHADOWING TECHNIQUE USING ELSA - Fatimatus Zahro'; Linda Uswatun Hasanah; Nadia Aulia Zuhriani; M. Husen Al Farisy; Fatimatus Zahro'; Linda Uswatun Hasanah; Nadia Aulia Zuhriani; M. Husen Al Farisy (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2026)
English speaking ability is an essential skill for students; however, pronunciation errors are still commonly found in English learning. To address this issue, the use of technology-based learning applications such as ELSA Speak combined with the Shadowing Technique can be an effective solution. This study was conducted at SMA Negeri 1 Balen involving 29 eleven-grade students. The research employed a quantitative approach using pre-tests, post-tests, and questionnaires as research instruments.The pre-test was administered to measure students’ initial pronunciation ability. Afterward, students received pronunciation practice using the ELSA Speak application through the Shadowing Technique. At the end of the treatment, a post-test was conducted to measure students’ improvement. The results showed a significant increase in students’ pronunciation scores, with the mean score improving from 66.62 in the pre-test to 83.72 in the post-test. These findings indicate that the Shadowing Technique using the ELSA Speak application is effective in improving students’ pronunciation mastery.In addition, the questionnaire results revealed that students had positive perceptions of the learning process. Most students stated that they enjoyed using the application and felt more confident in practicing pronunciation. Therefore, this study suggests that the combination of ELSA Speak and the Shadowing Technique can be a useful tool for teaching pronunciation in English learning.